Hydrothermal Synthesis of Superfine Strontium Titanate Particles - Qian, Qian; Liu, Yin; Chen, Chen; Zhang, Peiliang; Jiao, Baoxiang; Hou, Guihua (Asian Journal of Chemistry, 2014)
The superfine strontium titanate (SrTiO3) particles was successfully synthesized by hydrothermal method using KTiO(C2O4)2·3H2O, Sr(NO3)2 as raw materials and NaOH as mineralizer. The as-prepared samples were examined by X-ray powder diffraction for crystalline phase identification and scanning electron microscopy for particles morphology. The results show that the single phase of SrTiO3 could be obtained at 200 ºC for 12 h as the molar ratio of raw materials and mineralizer was 1:6. The hydrothermal temperature was the main reason which affected the crystal growth rate.